Intelligent control of clutch judder and shunt phenomena in vehicle drivelines. (4th August 2014) - Rabeih, E.M.A.; Crolla, D.A.
In the area of vehicle refinement, noise and vibrations associated with the driveline have been important sources of problems. Such noise and vibration phenomena are subjectively associated with judder, harshness or 'lack–of–refinement' complaints by customers. In a mathematical analysis, it is shown how friction gradient coefficient, effective system damping, clutch and driveline compliances, clutch engagement details and other driveline parameters affect the overall driveline behaviour. Particular problems are associated with clutch judder and torsional vibration instabilities during start–off or gear change manoeuvres. With the recent interest in automatic control of manual gearboxes, clutchless–shift systems and clutch modulation during take–up, it is shown that it should be possible in principle to avoid such refinement problems by controlling the clutch modulation using robust and adaptive control algorithms.